Customer Service Management Strategies In The E-Commerce Era: Enhancing Customer Loyalty Through Digital Experiences - Jamaluddin; Roslina Alam; St. Hatidja; Lina Mariana (Maneggio, 2024)
This study aims to analyze the role of digital marketing strategies in increasing customer loyalty in the e-commerce industry. In the rapidly evolving digital era, e-commerce companies are increasingly relying on technology to strengthen customer relationships and build long-term loyalty. This research highlights several key factors, such as personalization of marketing messages, digital technology-enabled loyalty programs, active interaction through digital platforms, as well as smart use of customer data. In addition, active interaction through social media and chatbots facilitates real-time communication, which increases customer satisfaction and their loyalty. The use of customer data allows companies to understand customer behavior and preferences, so they can tailor the customer experience more effectively. This study aims to analyze the role of digital marketing strategies in increasing customer loyalty in the e-commerce industry. In the rapidly evolving digital era, e-commerce companies are increasingly relying on technology to strengthen customer relationships and build long-term loyalty. This research highlights several key factors, such as personalization of marketing messages, digital technology-enabled loyalty programs, active interaction through digital platforms, as well as smart use of customer data. Personalization of marketing strategies can improve message relevance and customer experience, while digital loyalty programs provide incentives that drive engagement and strengthen customer relationships. In addition, active interaction through social media and chatbots facilitates real-time communication, which increases customer satisfaction and their loyalty. The use of customer data allows companies to understand customer behavior and preferences, so they can tailor the customer experience more effectively.